PERILAKU APARATUR DALAM PEMBUATAN KTP DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN NATUNA - E.21110093, Erwandi (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The writing of this article focuses on the behavior of personnel in making ID cards aretrying to be solved by the method of qualitative and descriptive presentation done with.With case studies in the Department of Population and Civil Registration Natuna regency.Based on the results of the study found there were less friendly attitude and irreverentindicated by the section officer ID card service in the Department of Population and CivilRegistration District Natuna role in terms of serving the public, and there is stilldiscrimination in providing services, the ability of workers to complete the job is still lessthan that seen no certainty. On the other hand they also found self motivated personnel islow, like the discipline in the office and break the tang melibihi predetermined time. Whilethe motivation of the leadership which is still less demonstrated by awards to officers towork better.Therefore, the researcher recommends that unit leaders can encourage, mobilize, andprovide rewards proportionately so that the officer can show a better attitude, friendly andpolite in serving the community and there is no selective logging, is also expected that moreworkers improve their skills, motivated to improve disciplinary work as well as expectedalso to the leaders to give more attention to the section officer ID card.Â Â Keywords: Apparatus Attitude, Ability and Motivation Apparatus Apparatus.Â